Photographic equipment distortion as the quality degradation factor of the International Space Station onboard images of the Earth surface stitching and georeferencing - Lamaka, Aliaksei A.; Davidovich, Yury S.; Rasskazov, Igor V. (Journal of the Belarusian State University. Physics, 2023)
The work is devoted to assessing the influence of the photographic equipment installed on board of the International Space Station distortion effects on the results of the Earth’s surface images recorded by this photographic equipment automatic alignment, as well as on the results of automated georeferencing. The used approach to distortion correction in images is described. The methods used for automatic image stitching using the OpenCV computer vision library, as well as methods for automated images georeferencing based on their correlation with Sentinel-2 geotagged satellite data using the ArcGIS software package, are described. The results of estimating the errors of photographic images stitching using various algoritms for highlighting singular points in images are presented with a comparison of data with and without distortion correction. The results of estimating the residuals of automated georeferencing using various methods of raster data transformation are presented with a comparison of the results for images with and without distortion correction. The need for distortion correction for photographic images obtained from the International Space Station is shown.
Keywords: computer vision; panoramic image; point detectors; point descriptors; ArcGIS